AN ANALYSIS OF SAYING TEXT IN DAILY METRO TABAGSEL - Ahmad Ripai Rangkuti (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
The objective of the research is to find out the system network of saying text in the newspaper of “Metro Tabagsel”. It was analyzed by analyzing speech function and its moods. Data was taken from texts found in Daily Metro Tabagsel which published in 1 February 2016. In analyzing the data, descriptive analysis was used. to draw the realization of speech function to its mood. The data analysis was formulated in some steps as identifying texts in Daily Metro Tabagsel; identifying the saying texts in Daily Metro Tabagsel, The realization of speech functions in mood in the text. The result shows that the dominant speech function of statement more than 30% includes into Information which is 31.25%. It is followed by Affirmation and Fury type of statement which have 12.5%. While the clarification, suggestion, achievement, Aim, threat,Promise and hope placed in the last rank which has 6.25%, It is indicated that this text always using information in the newspaper.